The historical origins of aridity and vegetation degradation in southeastern Spain - Carrión, J. S. S.; Fernández, S.; Jiménez-Moreno, G.; Fauquette, S.; Gil-Romera, G.; González-Sampériz, P.; Finlayson, C. (Journal of Arid Environments, 2010)
The complex relationships within modern landscapes cannot be understood without the beneﬁt of retrospective studies. We review palaeoenvironmental data for southeastern Spain, a landscape vulnerable to desertiﬁcation and with antiquity of human pressure on the landscape. A xerophytic component is discernible in the pollen diagrams of the southeastern peninsula ever since the Middle Miocene. During glacial stages of the Pleistocene, mountain grasslands and lowland steppes expanded, but tree vegetation, although episodically contracted, was ever present across the region, explaining part of the modern plant-species diversity. The magnitude of human impacts on vegetation during the Holocene has been highly variable, starting earlier (e.g. after c. 5000 cal years BP) in low-elevation areas and river basins. Forest degradation of the mountains started rather late during the Argaric period, and reached its maximum during the Roman occupation. Over the last millennia, natural and/or human-set ﬁres, combined with overgrazing, probably have pushed forests over a threshold leading to the spread of grassland, thorny scrub, junipers, and nitrophilous communities. The high degree of xerophytization observed today in southeastern Spain results from the long-term determinism of the Mid to Late Holocene climate aridiﬁcation, and the contingency of historical factors like ﬁre events and changes in prehistoric local economies involving resource exhaustion.
Keywords: historical biogeography; Holocene; palaeoecology; quaternary; Spain; Tertiary